2023
DOI: 10.1186/s40364-023-00503-7
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of the RNA-editing enzyme ADAR1 in stem cell fate and function

Abstract: Stem cells are critical for organism development and the maintenance of tissue homeostasis. Recent studies focusing on RNA editing have indicated how this mark controls stem cell fate and function in both normal and malignant states. RNA editing is mainly mediated by adenosine deaminase acting on RNA 1 (ADAR1). The RNA editing enzyme ADAR1 converts adenosine in a double-stranded RNA (dsRNA) substrate into inosine. ADAR1 is a multifunctional protein that regulate physiological processes including embryonic deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 142 publications
0
7
0
Order By: Relevance
“…In addition to Western blotting, the mRNA levels of ADAR1 and ZBP1 were examined in various cell lines (Figure B). It has also been previously reported that ADAR1 inhibits the necroptosis pathway by inhibiting ZBP1 to downregulate RIPK3-mediated necroptosis in cancer. ,, Consequently, other marker proteins in necroptosis, such as RIPK1 and RIPK3, were monitored. While RIPK1 exhibited similar expression levels in both normal and cancer cells, in keeping with a previous report, RIPK3 expression was found to be absent in most of the cell lines derived from solid tumors, such as HeLa cells.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition to Western blotting, the mRNA levels of ADAR1 and ZBP1 were examined in various cell lines (Figure B). It has also been previously reported that ADAR1 inhibits the necroptosis pathway by inhibiting ZBP1 to downregulate RIPK3-mediated necroptosis in cancer. ,, Consequently, other marker proteins in necroptosis, such as RIPK1 and RIPK3, were monitored. While RIPK1 exhibited similar expression levels in both normal and cancer cells, in keeping with a previous report, RIPK3 expression was found to be absent in most of the cell lines derived from solid tumors, such as HeLa cells.…”
Section: Resultsmentioning
confidence: 97%
“…The acquired Z-PROTACs 1c – 17c were introduced into HeLa cells at 5 μg/mL via lipofectamine-mediated transfection, and cell lysates were collected for Western blot analysis. As demonstrated in Figure C, ADAR proteins exist in various isoforms; therefore, ADAR1, ADAR2, and ADAR3 containing the A to I deaminase and another Z-DNA binding protein, ZBP1, with a Z α domain, need to be detected in this experimental condition as well. Given the reported importance of Z α and Z β domains for Z-DNA binding, and the existence of distinct ADAR1 isoforms (Figure C), we conducted a specificity analysis of the Z-PROTACs to ascertain their capacity to degrade different isoforms. Encouragingly, Figure D reveals that Z-PROTACs 7c , 8c , and 9c exclusively induced the degradation of ADAR1 p110 and p150 isoforms, displaying pronounced specificity toward these ADAR1 protein variants over other isoforms and the ZBP1 protein, likely due to the differential presence of the Z-DNA-binding motif in different isoforms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The only other mammalian molecule containing a Zα domain is ZBP1 (Z-DNA binding protein 1) [ 46 , 109 ]. ADAR1 mutations can also affect ZBP1, which recognizes endogenous Alu element-derived dsRNA, leading to inflammatory transcription [ 110 , 111 ]. Immune tolerance occurs when cells mark immunogenic dsRNA as “self” through A-to-I RNA editing, thereby preventing an excessive immune response.…”
Section: Biological Functions Of Rna Editingmentioning
confidence: 99%